DPSK versus pilot-aided PSK MAP equalization for fast-fading channels. - Davis, L.M.
This letter compares pilot-aided phase-shift keyed (PSK) and differential PSK (DPSK) modulation when using new maximum a posteriori joint channel estimation and equalization receivers with frequency-selective fast-fading channels. We conclude that pilot-aided PSK has superior bit-error rate performance in this case. However, at low signal-to-noise ratio, performance is similar, and DPSK is competitive due to reduced receiver complexity
Keywords: DPSK; Bit-error rate performance; Differential PSK; Equalization; Fast-fading channels; Frequency-selective fast-fading channels; Maximum a posteriori joint channel estimation; Phase-shift keying; Pilot-aided PSK MAP equalization; Receiver complexity; Receivers; Signal-to-noise ratio